2021
DOI: 10.1002/pc.26344
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, mechanical, magnetic, and thermal properties of 3D printed functional polymeric structures modified with Fe2O3 nanoparticles

Abstract: The Fe 2 O 3 nanoparticle structures, which have many application areas such as electronics, marine, and aviation, have been studying extensively due to the compliance between organic polymer and inorganic Fe 2 O 3 nanoparticles. Nanocomposite structures are successfully produced in the desired complexity with the additive manufacturing method. In the current study, Fe 2 O 3 nanoparticles were doped into the photocurable resin at different concentrations (pristine, 0.25%, 0.5%, and 1% in wt), and the prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The mechanical and thermal properties of PA6/clay nanocomposite fabricated with SLS process were studied by Kim and Creasy, [21] who reported that clay nanoparticles increased the viscosity and mechanical properties of the nanocomposite. Analysis of the mechanical properties of nanocomposites produced by 3D printing has been also studied by Guaricela et al [22] and Aktitiz et al [23,24] A review of previous works on the polymer nanocomposites indicated that enhancement of the mechanical properties of nanocomposites fabricated by the SLS process has been recently came into consideration. However, the SLS process has not been used to produce PA6/CNT nanocomposite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical and thermal properties of PA6/clay nanocomposite fabricated with SLS process were studied by Kim and Creasy, [21] who reported that clay nanoparticles increased the viscosity and mechanical properties of the nanocomposite. Analysis of the mechanical properties of nanocomposites produced by 3D printing has been also studied by Guaricela et al [22] and Aktitiz et al [23,24] A review of previous works on the polymer nanocomposites indicated that enhancement of the mechanical properties of nanocomposites fabricated by the SLS process has been recently came into consideration. However, the SLS process has not been used to produce PA6/CNT nanocomposite.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical and thermal properties of PA6/clay nanocomposite fabricated with SLS process were studied by Kim and Creasy, [ 21 ] who reported that clay nanoparticles increased the viscosity and mechanical properties of the nanocomposite. Analysis of the mechanical properties of nanocomposites produced by 3D printing has been also studied by Guaricela et al [ 22 ] and Aktitiz et al [ 23,24 ]…”
Section: Introductionmentioning
confidence: 99%
“…Several procedures are established depending upon different types of material like polymers and their nanocomposites. [33][34][35][36] Following, we introduce the working principles for the most relevant AM processes discussed in the subsequent sections.…”
Section: Additive Manufacturing Methodsmentioning
confidence: 99%
“…Finally, Aktitiz et al produced nanocomposite structures of resin, via the additive manufacturing method, doped with Fe 2 O 3 nanoparticles [ 120 ]. Fe 2 O 3 nanoparticles were added to the matrix in different concentrations.…”
Section: Characterization Of Polymer Nanocomposites For Aerospace Ind...mentioning
confidence: 99%
“…This improvement can reorganize the polymer chains’ degradation, movement, and thermal cracking. This work concluded that 3D-printed nanocomposites doped with Fe 2 O 3 nanoparticles could be considered a suitable material for applications with good thermal and magnetic properties desired, such as aerospace applications [ 120 ].…”
Section: Characterization Of Polymer Nanocomposites For Aerospace Ind...mentioning
confidence: 99%